CDx, NGS and regulation: five perspectives from the Pistoia Alliance. Issue 11 (November 2019) - Wise, John; Furness, Mike; McWilliams, Stewart; Patton, Simon
Highlights: Precision medicine will improve drug effectiveness and patient experience. The success of precision medicine hinges on the availability of companion diagnostics (CDx). The EU In Vitro Diagnostic Regulation (IVDR) came into effect in May 2017. The EU IVDR aims to improve the quality of CDx with more-rigorous CE marking. Biopharma will need to overcome many hurdles to access CE-marked CDx. Abstract : Companion diagnostics (CDx) are essential to the practice of precision medicine. Next-generation sequencing is an increasingly important tool in the development of CDx. However, for CDx to be deployed, many different biopharma industry sectors need to collaborate. This paper outlines some of the challenges and opportunities perceived by the biopharmaceutical industry, the Europe Molecular Quality Network, a regulatory agency, a notified body and a CDx service provider.